Compressive Strength and Microstructure Properties of Polymeric Concrete Incorporating Pulverized Fuel Ash (PFA) and Microwave Incinerated Rice Husk AshMIRHA) - Siti Asmahani Binti Saad, Siti Asmahani (Universiti Teknologi Petronas, 2009)
Polymeric concrete, the greener concrete attracts the attention of many parties in order to reduce the global warming problem caused by emission of CO2 in Portland cement production. Annually, million tons of fly ash is generated causing disposal problem because they require proper landfilling process and is very costly. On the other hand, large amount of rice husk are produced annually in Malaysia. Rice husk is highly resistant to natural degradation that can threaten the environment. However, the rice husk ash contains high amount of silica that can increase the durability of concrete.This project focuses on determination of cement-free polymeric concrete capacity as an alternative to Ordinary Portland Cement concrete (OPC) for in-situ casting and the effect of utilizing waste material in polymeric concrete. Pulverized Fuel Ash (PFA) is used as the main constituent and MIRHA as replacement by 0%, 3%, 5% and 7%. Sodium hydroxide and sodium silicate solution are used as alkali activators of silica (Si) and aluminium (Al) in main binders while sugar is added to delay the setting time of the polymeric concrete. The polymeric concrete samples are exposed to three different curing regimes namely hot gunny sack curing, ambient temperature curing and external exposure curing. Compressive strength test is carried out in 3,7,28 and 56 days to identify the strength of the polymeric concrete. Scanning Electron Microscopy (SEM) analysis is done to ascertain the microstructure properties of the produced polymeric concrete. It is concluded that external curing regime is the optimum curing method for in-situ casting in polymeric concrete production. Compressive strength of polymeric concrete in external exposure curing method reaches up to 48.88 MPa at 28 days.